The Basic Arithmetic of Legislative Decisions. Issue 2 (23rd April 2014) - Laver, Michael; Benoit, Kenneth
<x xml:space="preserve">Abstract</x> Despite the huge number of possible seat distributions following a general election in a multiparty parliamentary democracy, there are far fewer classes of seat distribution sharing important strategic features. We define an exclusive and exhaustive partition of the universe of theoretically possible n‐party systems into five basic classes, the understanding of which facilitates more fruitful modeling of legislative politics, including government formation. Having defined a partition of legislative party systems and elaborated logical implications of this partition, we classify the population of postwar European legislatures. We show empirically that many of these are close to critical boundary conditions, so that stochastic processes involved in any legislative election could easily flip the resulting legislature from one type to another. This is of more than hypothetical interest, since we also show that important political outcomes differ systematically between the classes of party systems—outcomes that include duration of government formation negotiations, type of coalition cabinet that forms, and stability of the resulting government.